The cross-entropy method and its application to minimize the ripple of magnetic levitation forces of a maglev system - Zhang, Wei; Yang, Shiyou; Bai, Yanan; Machado, Jose Marcio [UNESP] (IOS Press, 2010)
This paper explores firstly the potential of a new evolutionary method - the Cross-Entropy (CE) method in solving continuous inverse electromagnetic problems. For this purpose, an adaptive updating formula for the smoothing parameter, some mutation operation, and a new termination criterion are proposed. The proposed CE based metaheuristics is applied to reduce the ripple of the magnetic levitation forces of a prototype Maglev system. The numerical results have shown that the ripple of the magnetic levitation forces of the prototype system is reduced significantly after the design optimization using the proposed algorithm.
Keywords: Cross-entropy method; global optimization; design optimization; Evolutionary algorithm